Preferred Habitat, Policy, and the CIP Puzzle - Paul Wohlfarth (Birkbeck, University of London, Birkbeck Centre for Applied Macroeconomics (BCAM), 2019)
A crucial no-arbitrage condition on foreign exchange markets, covered interest parity (CIP),held almost exactly before the Global Financial Crisis (GFC) and failed since then. CIP deviations have been particularly puzzling in relatively calm markets after 2014. This paper explains deviations from CIP, measured by the cross-currency basis from swaps (CCBS), in terms of significant policy and volatility effects in a preferred habitat model of the Eurodollar swap market. Estimation is done using EGARCH in mean for a set of CCBS maturities. The term structure of the CCBS is further analysied in a Vector Error Correction Model(VECM).
Keywords: E43; E44; E5; F31; G12; G15; 330; Macro Finance; International Monetary Economics; Preferred Habitat; Foreign Exchange Markets; International Finance